2015
DOI: 10.1093/mnras/stv1572
|View full text |Cite
|
Sign up to set email alerts
|

Kepler's first view of O-star variability:K2data of five O stars in Campaign 0 as a proof of concept for O-star asteroseismology

Abstract: We present high-precision photometric light curves of five O-type stars observed with the refurbished Kepler satellite during its Campaign 0. For one of the stars, we also assembled high-resolution ground-based spectroscopy with the hermes spectrograph attached to the 1.2-m Mercator telescope. The stars EPIC 202060097 (O9.5V) and EPIC 202060098 (O7V) exhibit monoperiodic variability due to rotational modulation with an amplitude of 5.6 mmag and 9.3 mmag and a rotation period of 2.63 d and 5.03 d, respectively.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 60 publications
0
49
0
Order By: Relevance
“…Even though this is below our region of attention, but it is worth to mention that recently Balona et al (2015) predicted that a factor 2 increase in the Fe opacity around log T ∼ 5.06 can destabilize (2013) and references therein, (b) Buysschaert et al (2015): the star has a poorly known fundamental parameters due to its binary nature, poor quality spectra and inadequate orbital monitoring; thus, we assumed 2 000 K uncertainty in T eff and 0.5 dex in log g, (c) Thoul et al (2013), (d) Briquet et al (2013): it is the only magnetic and rapid rotator (50% critical) here, and its position on the Kiel diagram is less secure, (e) CoRoT target (Conny Aerts, private communication).…”
Section: Revised Instability Strips Of the Upper Hr Diagrammentioning
confidence: 80%
“…Even though this is below our region of attention, but it is worth to mention that recently Balona et al (2015) predicted that a factor 2 increase in the Fe opacity around log T ∼ 5.06 can destabilize (2013) and references therein, (b) Buysschaert et al (2015): the star has a poorly known fundamental parameters due to its binary nature, poor quality spectra and inadequate orbital monitoring; thus, we assumed 2 000 K uncertainty in T eff and 0.5 dex in log g, (c) Thoul et al (2013), (d) Briquet et al (2013): it is the only magnetic and rapid rotator (50% critical) here, and its position on the Kiel diagram is less secure, (e) CoRoT target (Conny Aerts, private communication).…”
Section: Revised Instability Strips Of the Upper Hr Diagrammentioning
confidence: 80%
“…Frequency ν 8 = 1.599(3) d −1 in our list is not detected by them. The differences can largely be explained by the extraction and detrending procedure; Buysschaert et al (2015) did not use k2sc. This highlights the importance and impact of detrending on extracted pulsation modes in variable stars and any subsequent frequency analysis.…”
Section: Epic 202060092 -Hd 256035mentioning
confidence: 99%
“…For EPIC 202060092, estimates of the effective temperature and surface gravity are provided by Buysschaert et al (2015) so we use that value instead. For EPIC 20269110 and EPIC 202929357 the spectral type classification was assigned OB − by Drilling & Bergeron (1995).…”
Section: Appendix B: Gaiamentioning
confidence: 99%
“…Methodologies to account for systematic variability caused by the spacecraft thruster firings are continuously being developed (Vanderburg & Johnson 2014;Aigrain et al 2015;Angus et al 2015;Huang et al 2015;Lund et al 2015) and have demonstrated that the photometric precision of K2 is at least within a factor of two of Kepler. Early K2 science results include the discovery of exoplanets around bright GKM dwarfs (Crossfield et al 2015;Foreman-Mackey et al 2015;Petigura et al 2015;Vanderburg et al 2015), eclipsing binary stars (Armstrong et al 2015;LaCourse et al 2015), as well as the detection of pulsations across the HR diagram such as subgiants , red giants (Stello et al 2015), white dwarfs (Hermes et al 2014), RR Lyrae stars (Molnár et al 2015;Kurtz et al 2016), O stars (Buysschaert et al 2015), and subdwarf B stars (Jeffery & Ramsay 2014).…”
Section: Introductionmentioning
confidence: 99%